Assessing the Advancement of the Social and Environmental Aspects of Islamic Banking Development in Indonesia - Pratama, Yoghi Citra; Nazhirah, Naila (Research Synergy Foundation, 2025)
Islamic banking is fundamentally rooted in Islamic values and guided by Maqasid Shariah (Shariah objectives), which emphasizes goals applicable to both social and commercial activities. This framework reflects the dual objectives that Islamic banks strive to achieve, as stipulated in Islamic Banking Law No. 21 of 2008. Furthermore, this social objective is in line with the international Sustainable Development Goals (SDGs). This research explores the progress of Islamic banks in Indonesia in relation to their contributions to social and environmental aspects. It seeks to analyse the impact of Islamic banking practices on social welfare and sustainable development within the Indonesian context. To support this analysis, stakeholder theory is adopted in conjunction with the Reactive, Defensive, Accommodative, and Proactive (RDAP) scale. The RDAP scale functions as a comprehensive instrument for assessing the social performance of Islamic banking through content analysis, relying on the annual reports of 12 Islamic banks to evaluate their social contributions. The findings indicate that Islamic banks consistently associated with high social outcomes are typically not affiliated with conventional banks or characterised by large capital, such as BSI Bank Aceh Syariah and Bank NTB Syariah. This insight implies the need for regulators to provide incentives aimed at enhancing the social outcomes of Islamic banks.